Customs ports of Great Britain : transcripts
Volume of copies of Exchequer documents (1815-1846) and Treasury warrants (1847-1908) regarding the boundaries and limits of customs ports.
Collection material in English.
Keywords: Great Britain. -- Exchequer; Great Britain. -- Treasury; Ports of entry -- Great Britain